Research Status and Development Direction of Smart Clothing Materials - LI Xiaolei; SHAN Yufu; QIAN Xiaoming; SHI Yunlong (东华大学学报（英文版）, 2022)
TS941; With the continuous development of technology and society, smart devices have filled people' s lives and become an indispensable part of people's lives. At the same time, smart clothing has also been greatly developed. This article introduces several smart clothing materials, analyzes the current research status of smart clothing materials, and further discusses the applications of smart clothing materials in military, medical, intelligent decoration, and sports and leisure fields. Then the problems of smart clothing in safety, environmental protection, and industrial technology are analyzed, and the corresponding solutions to these problems are proposed, so as to provide reference and guidance for the future development of smart clothing in China. And the research shows that smart clothing will develop in the direction of fashion and diversification, function and comfort, safety and environmental protection, convenience and low cost in the future.